THE TRAINING OF COMPETENCES FOR MANAGEMENT IN NURSING - Maria de Lourdes de Almeida; Aida Maris Peres; Elizabeth Bernardino; Marieta Fernandes Santos (Universidade Federal do Paraná, 2014)
The objective of this exploratory-descriptive study was to identify the knowledge, skills and attitudes learned by 22 graduates from an undergraduate course in the issue of Management in Nursing. The data collection period was February - April 2010; for data analysis it used the technique of the Discourse of the Collective Subject, which is based on Social Representation Theory. Results: Discourses of the Collective Subject appeared referent to the use of managerial instruments in managerial actions: knowledge regarding management of human, material, physical, environmental and nursing care related resources; managerial skills such as communication, continuous education, and decision-making; problem resolution and leadership; and attitude based on knowledge and influenced by the institutional role of nursing. The teaching of management at the undergraduate level stands out through the support which this provides for the development of knowledge, skills and attitudes which form a base for managerial practice in nursing.